The Influence of Service Quality Dimensions and E-Commerce Image on User Satisfaction Levels - Putera, Wayan Andrika; Cipta, I Putu Agus Eka Yatna; Yudistira, I Gede Angga; Puspita, Ni Wayan Diah; Pramesti, Indra Eka Bintang (Sinkron : jurnal dan penelitian teknik informatika, 2025)
This study investigates how service quality and brand image influence user satisfaction on Shopee, Indonesia’s leading e-commerce platform, amid persistent operational challenges like delivery delays and inefficient return processes. Using a quantitative approach, data was collected via validated questionnaires and analysed through multiple regression, with diagnostic tests ensuring model reliability. Results show both service quality and brand image significantly boost satisfaction, with brand image having nearly twice the impact. The model’s high explanatory power, with adjusted R² is 0.943, confirms their dominant role in shaping user experiences. These findings align with prior retail and hospitality studies but challenge traditional service-dominant logic by highlighting brand perception as the stronger driver in digital commerce. For practitioners, this underscores the need to prioritize brand-building strategies, such as trust signals and influencer partnerships, while maintaining service standards. However, the study’s exclusive focus on Shopee limits generalizability, calling for future cross-platform comparisons. Additional research should employ longitudinal designs, examine cultural moderators, and apply advanced analytics to uncover deeper satisfaction dynamics. By validating the interplay of service quality and brand equity in e-commerce, this study advances theoretical discourse while offering actionable insights for platforms seeking to enhance customer satisfaction in competitive digital marketplaces.